Centro de Educación Básica Especial para niños Tea en San Juan de Lurigancho - Paz Colina, Samantha Mialu (2021)
The project to be presented is the result of research on pedagogy and educational infrastructure aimed at children with Autism Spectrum Disorder - ASD, both of which are factors that allow and support the development of their social and cognitive skills. In the present, the lack of premises and inadequate infrastructure corresponding to ASD education is evaluated and evidenced, proposing an alternative that comply the basic needs of a special education center, as well as the needs of an ASD child. Likewise, theories are reviewed and national and international benchmark projects are evaluated considering new alternatives to formulate a proposal in response to the main objectives of the project. Although ASD education for children requires special advice at the pedagogical level, it also needs to be reinforced with an environment that can increase the effectiveness of special education. This project tries to satisfy the needs that currently exist in national special education, specifically in the infrastructure of special basic education centers.